Social Stock Exchange – An Innovative Mechanism for Philanthropy through Bourse - ARSHDEEP, Arshdeep; SHARMA, Nishi; JINDAL, Kiran; SHARMA, Meena (Theoretical and Practical Research in Economic Fields, 2025)
Purpose : Two decades ago, Brazil established a formal social stock exchange, followed by several other countries. This unique concept links social enterprises with philanthropic investors, but their success rate is low. This paper analyzes the mechanisms of social stock exchanges in different countries and identifies factors affecting their success. Design: The present study is exploratory in nature whereby an attempt has been made to understand the framework of social stock exchanges established across the globe. Findings: The failure of social stock exchanges in Brazil, South Africa, Portugal, and the UK can be attributed to lack of investor awareness, higher economic cost for registered social enterprises and limited funding options in less diversified projects. However, the model of SSE is operational in other three countries apart from India. Originality: The concept of the social stock exchange is in the infancy stage and limited work has been done in this domain. The present paper attempts to make a significant contribution to the literature by providing a detailed analysis of such exchanges. Research limitations: The present paper is based on secondary data and inclusion of primary data can augment the findings. Practical implications: SSEs can be miraculous in addressing financial constraints in social enterprises but the concept still could not get momentum. The present paper aims to address challenges that hinder the success of these exchanges. Social implications: The findings of the study could improve the functioning of these exchanges, thereby supporting the financing of enterprises aimed at socio-economic upliftment in the deprived sections.